The SFRY did not fall apart – it was intentionally broken up - Atlagić, Marko; Martinović , Aleksandar (Napredak, 2021)
In this paper we propose that in the 1990s the SFRY did not fall apart but was broken up because, in the opinion of the US, the reasons for its existence disappeared. The Americans believed that the SFRY was created as a barrier against Soviet expansion in the West. As the bipolar world dissolved and the era of globalization began, the need for the existence of the SFRY disappeared. This was the reason why the country needed to be broken up. The authors are of the opinion that the SFRY was broken up by the USA, Germany, the Vatican, other Western countries and the secessionist Yugoslav republics, Slovenia and Croatia. For this reason, these countries bear the historical responsibility for breaking up a sovereign state, in opposition to its constitution, the UN Charter and the Helsinki Accords.
Keywords: SFRY; USA; Germany; the Vatican; NATO; Slovenia; Croatia